Sistem Pendukung Keputusan Pemberian Bonus Berdasarkan Penilaian Kinerja Karyawan di PT. Alita Praya Mitra dengan Metode AHP - Yuli Haryanto (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
Employees are one of the resources used as a driving force in advancing a company. Employees are one of the main factors in the smooth running, progress and success of a company. In every company, agency, organization or business entity will provide a salary as compensation for the performance of an employee. In addition, there are many companies that reward employees by giving bonuses based on employee performance that is considered satisfactory to the Company with the aim of motivating employees to work even harder. Therefore, an application is made using a decision support system that can determine the provision of annual bonuses to employees using the Analytical Hierarchy Process method. This application is expected to be able to help determine employees who are entitled to an annual bonus.